International seminars on innovation in the railway system (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of an international seminar conference held at the Basel Convention Centre in December 1996. In five parts.